Design and investigation of dielectric modulated triple metal gate-oxide-stack Z-shaped gate horizontal pocket TFET device as a label-free biosensor. (1st August 2022) - Reddy, Nelaturi Nagendra; Panda, Deepak Kumar
Abstract: In this article, a dielectric modulated triple metal gate-oxide-stack Z-shaped gate horizontal source pocket tunnel field-effect transistor (DM-TMGOS-ZHP-TFET) structure has been investigated for the application of label free-biosensor. This work explores the advantage of gate work function engineering along with the gate-oxide-stack approach for the ZHP-TFET for the first time. An asymmetric nano-cavity is created adjacent to the source-channel junction to immobilize the target biomolecules conjugation to the proposed device. The sensitivity of the device is thoroughly investigated in terms of average subthreshold swing (SS), threshold voltage ( V th ) and the switching ratio ( I on / I off ) of the proposed device with the variation of the dielectric constant value inside the nano-gap under the gate electrode. The device characteristics are investigated with different combinations of metal work functions to match the desired feature and sensitivity of the device. In addition, the sensitivity analysis of the proposed device is analyzed in the presence of both positive and negative charged biomolecules in the cavity region to study the charge effect on label-free detection of the device. A comparative study is conducted between a single metal gate (SMG) ZHP-DM-TFET biosensor with the DM-TMGOS-ZHP-TFET biosensor explores the advantage of gate-work function engineering with a gate-oxide-stack approach. Interestingly the DM-TMGOS-ZHP-TFET biosensor shows superior results with a high current ratio sensitivity of 10 3 which is ten times more than the SMG-ZHP-DM-TFET biosensor and this device also exhibits low subthreshold characteristics.